2021
DOI: 10.1101/2021.11.12.468444
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic induction of appetitive and aversive taste memories in Drosophila

Abstract: SUMMARYTastes are typically thought to evoke innate appetitive or aversive behaviours, prompting food acceptance or rejection. However, research in Drosophila melanogaster indicates that taste responses can be modified through experience-dependent changes in mushroom body circuits. In this study, we develop a novel taste learning paradigm using closed-loop optogenetics. We find that appetitive and aversive taste memories can be formed by pairing gustatory stimuli with optogenetic activation of sensory or dopam… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
(129 reference statements)
0
5
0
Order By: Relevance
“…Because behavioral modulation in our paradigm does not require simultaneous exposure to both tastes, the underlying circuit mechanisms are likely to be distinct from those previously described. Indeed, we found that prolonged PER modulation in our paradigm does not require the mushroom body, which mediates associative taste learning ( Kirkhart and Scott, 2015 ; Masek et al., 2015 ; Jelen et al., 2021 ).…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…Because behavioral modulation in our paradigm does not require simultaneous exposure to both tastes, the underlying circuit mechanisms are likely to be distinct from those previously described. Indeed, we found that prolonged PER modulation in our paradigm does not require the mushroom body, which mediates associative taste learning ( Kirkhart and Scott, 2015 ; Masek et al., 2015 ; Jelen et al., 2021 ).…”
Section: Discussionmentioning
confidence: 66%
“…Most studies have investigated cross-modulation between different taste modalities when they are presented at overlapping times. Different tastes presented together are acutely integrated to determine behavior ( Wang et al., 2004 ; Inagaki et al., 2014 ) and can modulate future responses through associative learning ( Kirkhart and Scott, 2015 ; Masek et al., 2015 ; Jelen et al., 2021 ). Because behavioral modulation in our paradigm does not require simultaneous exposure to both tastes, the underlying circuit mechanisms are likely to be distinct from those previously described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations